COVID-19: One year together - A. N. Lukashev (Журнал инфектологии)
The pandemic of COVID-19, a novel respiratory infection, has become one of the most significant events in the history of infectious diseases over the past 100 years. The article reviews the main stages in the development of a pandemic and the fight against it, the most appealing issued faced by medical science, the successes and mistakes of healthcare systems and researchers, the current state of the problem and the nearest prospects.